A modular design strategy to integrate mechanotransduction concepts in scaffold-based bone tissue engineering. (December 2020) - Entezari, Ali; Swain, Michael V.; Gooding, J. Justin; Roohani, Iman; Li, Qing
Abstract: Repair or regeneration of load-bearing bones has long been an incentive for the tissue engineering community to develop a plethora of synthetic bone scaffolds. Despite the key role of physical forces and the mechanical environment in bone regeneration, the mechanotransduction concept has rarely been incorporated in structural design of bone tissue scaffolds, particularly those made of bioactive materials such as hydrogels and bioceramics. Herein, we introduce a modular design strategy to fabricate a load bearing device that can support a wide range of hydrogel- and ceramic-based scaffolds against complex in-vivo loading conditions to induce desirable mechanical strains for bone regeneration within the scaffolds. The device is comprised of a fenestrated polymeric shell and ceramic structural pillars arranged in a sophisticated configuration to provide ample internal space for the scaffold, also enabling it to purposely regulate the levels of strains and stresses within the scaffolds. Utilizing this top-down design approach, we demonstrate that the failure load of alginate hydrogels increases 3200-fold in compression, 300-fold in shear and 75-fold in impact, achieving the values that enable them to withstand physiological loads in weight-bearing sites, while allowing generation of osteoinductive strains (i.e., 0.2-0.4%) in the hydrogel. This modular design approach opens a broad range of opportunities to utilize various bioactive but mechanically weak scaffolds for the treatment of load-bearing defects and exploiting mechanobiology strategies to improve bone regeneration. Graphical abstract: Image, graphical abstract